Đặc điểm địa mạo động lực vùng cửa sông ven biển từ cửa Ba Lạt đến cửa Đáy và lân cận - Hùng, Phạm Văn; Hoài, Vũ Thị Thu (Vietnam Journal of Earth Sciences, 2009)
Characteristics of dynamic geomorphology of coastal-river mouth zones from Balat mouth to Day mouth and adjacent ...